Alexander Disease Mutations Produce Cells with Coexpression of Glial Fibrillary Acidic Protein and NG2 in Neurosphere Cultures and Inhibit Differentiation into Mature Oligodendrocytes - Gómez-Pinedo, Ulises; Sirerol-Piquer, Maria Salomé; Durán-Moreno, María; García-Verdugo, José Manuel; Matias-Guiu, Jorge (Frontiers in Neurology, 2017)
Background. Alexander disease (AxD) is a rare disease caused by mutations in the gene encoding glial fibrillary acidic protein (GFAP). The disease is characterised by presence of GFAP aggregates in the cytoplasm of astrocytes and loss of myelin. Objetives: Determine the efect of AxD-related mutations on adult neurogenesis Methods: we transfected different types of mutant GFAP into neurospheres using the nucleofection technique. Results: We find that mutations may cause co-expression of GFAP and NG2 in neurosphere cultures, which would inhibit the differentiation of precursors into oligodendrocytes and thus explain the myelin loss occurring in the disease. Transfection produces cells that differentiate into new cells marked simultaneously by GFAP and NG2 and whose percentage incresed over days of differentation. Increased expression of GFAP is due to a protein with an anomalous structure that forms aggregates thoughout the cytoplasm of new cells. These cells display down-expression of vimentin and nestin. Up-expression of cathepsin D and caspase-3 in the first days of differentiation suggest that apoptosis as a lysosomal response may be at work. HSP27, a protein found in Rosenthal bodies, is expressed less at the beginning of the process although its presence increases in later stages. Conclusion. Our findings seem to suggest that the mechanism of development of AxD may not be due to a function gain due to increase of GFAP, but to failure in the differentiation process may occur at the stage in which precursor cells transform into oligodendrocytes, and that possibility may provide the best explanation for the clinical and radiological images described in AxD.